If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2Cos(3x) + -1x + 24y = 0 Remove parenthesis around (3x) 2osC * 3x + -1x + 24y = 0 Reorder the terms for easier multiplication: 2 * 3osC * x + -1x + 24y = 0 Multiply 2 * 3 6osC * x + -1x + 24y = 0 Multiply osC * x 6osxC + -1x + 24y = 0 Solving 6osxC + -1x + 24y = 0 Solving for variable 'o'. Move all terms containing o to the left, all other terms to the right. Add 'x' to each side of the equation. 6osxC + -1x + x + 24y = 0 + x Combine like terms: -1x + x = 0 6osxC + 0 + 24y = 0 + x 6osxC + 24y = 0 + x Remove the zero: 6osxC + 24y = x Add '-24y' to each side of the equation. 6osxC + 24y + -24y = x + -24y Combine like terms: 24y + -24y = 0 6osxC + 0 = x + -24y 6osxC = x + -24y Divide each side by '6sxC'. o = 0.1666666667s-1C-1 + -4s-1x-1yC-1 Simplifying o = 0.1666666667s-1C-1 + -4s-1x-1yC-1
| y-9/2=y/5 | | 2Cos(3x)-x+24= | | 2p=-n | | 2y+12=-10x | | N/3=6.6 | | 12x-3=36+3 | | 11a-4a=Xa | | (3x+2)(x-4)-(3x+2)(x+8)=0 | | p+2n=0 | | 10b-2= | | 30=3n+1p | | 16=4y-12 | | 2x(3x-5)x=4 | | 6x+-6= | | 3÷5/3 | | 20=3n+1p | | 6x+-15= | | 6t-t+6= | | 2(x-8)-7x=-6 | | 2x(3x-5)forx=4 | | 10y-15+8y+2+6y+11=180 | | 5.825= | | N/m=8 | | 2x^3-19x^2+34x+22=0 | | 222=5z+4z+3 | | 5p-3+p= | | 3(7-2f)=31 | | 2(4)+y=-4 | | 4x^2y^5-8xy^3=0 | | 5[x+(x+1)]-10= | | 294-3.50/12=X | | 2(2)+y=-4 |